Ocular biometric parameters among Han and Uyghur young adults with myopia in Xinjiang, China - Xin-Rong Li; Wen-Bo Cheng; Lu-Mei Hu; Hai-Nan Zhang; Xing-Xing Peng; Xiang-Long Yi (International Journal of Ophthalmology)
AIM: To describe ocular biometric parameters among Han and Uyghur myopic adults in Xinjiang, China. METHODS: A cross-sectional study was conducted. The different ocular biometric parameters collected using Pentacam were analyzed, including corneal curvature, corneal astigmatism (CA), horizontal corneal diameter (white-to-white, WTW), corneal volume (CV), pupil diameter (PD), anterior chamber angle (ACA), anterior chamber depth (ACD), anterior chamber volume (ACV) and axial length (AL). RESULTS: In total, 2932 participants were included in the final analysis, comprising 2310 Han and 622 Uyghur adults. Adults in the high myopia (HM) group had steeper K2, larger CA, smaller WTW and longer AL in both the Uyghur and Han adults (all P<0.05). The moderate myopia (MM) and HM group had deeper ACV, ACD and wider ACA than the low myopia (all P<0.05) in Han adults, however there were no differences in anterior chamber indices with Uyghur adults. In the Uyghur adults, we noticed that CV, WTW, and ACD were smaller, ACA was narrower, PD was larger, and AL was shorter (all P<0.05). We also noticed sex differences: males had flatter corneas, deeper ACD and ACV, and larger WTW than females (all P<0.05). In the correlation analysis, WTW was positively correlated with ACD and ACV but negatively correlated with K1, K2 and CV (all P<0.05). Narrower ACA was associated with larger PD (rU=-0.25, rH=-0.16, all P<0.01). CONCLUSION: The Han population have different biometric parameters in eyes with HM compared to the Uyghur population, and the Uyghur population may anatomically more susceptible to primary angle closure glaucoma than the Han population.